Designing a Pedagogical Deep Learning-Oriented Problem-Based Learning E-Module for Human Circulatory System Learning: Development, Validation, and Students’ Responses - Ade Siti Khairunnisa Siregar; Nurkhairo Hidayati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop a Problem-Based Learning (PBL)-based e-module integrated with a Pedagogical Deep Learning approach, evaluate its feasibility, and examine students’ responses through a limited trial involving 36 students. The research was conducted at SMP Negeri 04 Siak Hulu using the ADDIE development model, with a particular focus on the development phase. The evaluation process involved four experts, consisting of one media expert, one subject-matter expert, and two learning experts. Data were collected using validation sheets and student response questionnaires and were analyzed through descriptive calculations of validation and response scores. The findings revealed that the developed e-module achieved a high level of validity, with average scores of 96% from the media expert, 91% from the subject-matter expert, and 92% from the learning experts. Furthermore, students’ responses yielded an average score of 94%, which was categorized as excellent. The e-module was specifically designed for circulatory system content in science education and featured an interactive interface that could be accessed both online and offline. These findings indicate that the PBL-based e-module integrated with a Pedagogical Deep Learning approach is a feasible and highly accepted instructional resource. Therefore, it is recommended as an innovative technology-enhanced learning material to support more effective, interactive, and meaningful learning experiences.